Promoting Family Health: A Community Internship Program on Interprofessional Education and Collaboration in Banjarsari District - Sasmita, Hanum; Jatmiko Rinto W; Nurmalisa, Baiq Emy (Jurnal Pengabdian Masyarakat Lentora, 2025)
Background: The Family Approach Healthy Indonesia Program (PIS-PK) is a key strategy of the Indonesian Ministry of Health. To support this program, community empowerment through interprofessional collaboration is essential. This activity was conducted in RW 05, Banjarsari District, which was identified as an area with specific health concerns.Objectives: This community service aimed to: 1) Implement interprofessional collaboration to address community health issues, and 2) Increase residents' knowledge and awareness of priority health problems.Methods: The activity used the IPCIdEM (Interprofessional Collaborative Practice in Education and Management) approach. The stages included: 1) Problem identification through Focus Group Discussions (FGDs) and analysis of Family Health Index (IKS) data; 2) Planning and implementation of interventions, which consisted of health screenings (blood pressure and blood sugar), health education sessions on hypertension, diabetes, stunting prevention, and family planning, and the distribution of iron supplements to adolescent girls; 3) Evaluation through pre-test and post-test.Results: The FGD and IKS data revealed three priority health problems: Non-Communicable Diseases (hypertension and diabetes), stunting risks, and low participation in family planning programs. The intervention showed positive outcomes: a total of 100 residents participated in the health screenings and education. Pre-test and post-test results from the NCD session showed a significant increase in the average knowledge score from 60% to 80%. Furthermore, 80% of participating adolescent girls committed to consuming iron tablets regularly.Conclusion: The IPCIdEM approach proved effective in facilitating interprofessional collaboration and improving community health literacy. This model can be replicated in other communities to tackle priority health issues in a structured and collaborative manner